2003
DOI: 10.1203/00006450-200301000-00017
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo-Controlled Comparison of Effects of Repetitive Doses of Betamethasone and Dexamethasone on Lung Maturation and Lung, Liver, and Body Weights of Mouse Pups

Abstract: The aim of this study was to compare in vivo effects of single and repetitive doses of betamethasone (BETA) and dexamethasone (DEX) administered to pregnant mice on lung maturation and lung, liver, and body weights (LLBW) of their pups. One hundred and eighty gravid Swiss albino mice were randomly assigned to 1 of 6 groups (n = 30) and administered either BETA, DEX, or saline as a single dose at 14 d gestation or repetitive doses twice daily at 14 and 15 d gestation. All the study groups were then divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The few direct comparisons of dexamethasone with betamethasone in developing annals also demonstrate differences in the drugs. For example, Ozdenir, et al, reported that betamethasone promoted more lung maturation with less growth restriction in fetal mice than did dexamethasone [10]. Pregnant sheep developed labor more consistently with fetal infusions with betamethasone than with dexamethasone, and the fetal betamethasone treatment decreased maternal progesterone more than dexamethasone [11].…”
Section: Current State Of Antenatal Steroid Usementioning
confidence: 99%
“…The few direct comparisons of dexamethasone with betamethasone in developing annals also demonstrate differences in the drugs. For example, Ozdenir, et al, reported that betamethasone promoted more lung maturation with less growth restriction in fetal mice than did dexamethasone [10]. Pregnant sheep developed labor more consistently with fetal infusions with betamethasone than with dexamethasone, and the fetal betamethasone treatment decreased maternal progesterone more than dexamethasone [11].…”
Section: Current State Of Antenatal Steroid Usementioning
confidence: 99%
“…Breathing scores were determined by two independent investigators by observing for 2 minutes pups placed on moistened filter paper at 378C immediately after removal from the mother. Scoring assignment was performed according to the criteria described by Ozdemir and colleagues (20).…”
Section: Scgb3a2 Protein and Animal Studiesmentioning
confidence: 99%
“…Early studies using rhesus monkeys demonstrated that maternal intramuscular betamethasone administration at 120-133 days of gestation (term is 167 days) resulted in significant reductions in fetal body weight of ~23% at 133 and 167 days of gestation. More recently, studies in sheep and mice demonstrated that clinically relevant doses of maternal betamethasone caused significant fetal growth restriction and reductions in the weight of most organs [87][88][89][90][91]. Growth restriction has also been shown in rats and rabbits treated with maternal dexamethasone [83][84][85][86].…”
Section: Growth Effectsmentioning
confidence: 99%